The Electric Vehicle Power Design and The Matching Characteristics Analysis of The Transmission System - Lei Zhang; Guili Hao; Xiumin Yang; Chunyang Zhou (Institute of Advanced Engineering and Science, 2013)
According to the requirements of the performance parameters of chongqing lifan E520 cars, electric vehicles with pure mechanical electronically controlled continuously variable transmission (CVT) were designed and developed. The power function of traction motor was designed firstly. According to the vehicle performance and motor parameters, matching parameters of CVT were calculated and confirmed. The parameters of maximum speed, acceleration time and gradeability of CVT were analyzed and compared. The parameters of the battery pack were designed according to the acceleration capability of electric vehicles, continued driving mileage. Currently, the electric vehicles equipped with pure mechanical electronically controlled CVT have passed the bench test and loading operation. These have proved that the dynamic design and driveline matching design in this paper were correct and achieved a predetermined operating performance and power performance indicator. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3801